A Drosophila growth factor homolog, decapentaplegic, regulates homeotic gene expression within and across germ layers during midgut morphogenesis. - Panganiban, G.; Reuter, R.; Scott, M.P.; Hoffmann, F.M. (Development, 1990)
The decapentaplegic (dpp) gene product, a member of the transforming growth factor-beta family, is required in Drosophila embryos for normal gastrulation and the establishment of dorsal-ventral polarity in the embryo. dpp is also expressed at specific positions in the visceral mesoderm along the developing midgut. We find that mutations that eliminate the visceral mesoderm expression of dpp lead to defects in midgut morphogenesis and alter the spatially localized expression of the homeotic genes Sex combs reduced (Scr), Ultrabithorax (Ubx), and Antennapedia (Antp) in the visceral mesoderm. The extracellular dpp protein migrates from the visceral mesoderm across the apposing endodermal cell layer in a region of the endoderm that expresses the homeotic gene labial (lab). Mesodermal expression of dpp is required for the expression of lab in these endodermal cells indicating that dpp mediates an inductive interaction between the two germ layers. We propose that extracellular dpp protein regulates gut morphogenesis, in part, by regulating homeotic gene expression in the visceral mesoderm and endoderm of the developing midgut.